Analisis Pengawasan Melekat (WASKAT) terhadap Kinerja Pegawai di Kantor Lurah Bukit Kapur Kota Dumai - Dwi Nuha Nabilah; Siti Nurlaila; Suci Aulia; Nurmala Sari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study analyzes the effectiveness of installed supervision (Waskat) by the Sub-district Head on the performance of employees at the Bukit Kapur District Office, Dumai City, in the midst of the demands of public service accountability. The background involves local bureaucratic challenges such as resource constraints and employee resistance. Using a qualitative approach with field observation for two weeks (15-29 December 2025), including in-depth interviews with 5 employees and 2 community informants, plus data triangulation from attendance records and performance reports, it was analyzed thematically. The results revealed attendance increased to 95%, absenteeism decreased by 2%, and work output increased from 50 to 65 permit documents each week. Quotes such as